Biology microteaching book: A practical approach from various countries - Siburian, Jodion; Sadikin, Ali (Universitas Negeri Jakarta, 2022)
Pre-service Biology teachers must be equipped with good biology skills, 21st-century teaching skills currently needed, and possess four competencies (pedagogic, professional, personality, and social). The study aims to develop a biology microteaching book to create competent, confident, and creative biology teachers with a practical approach. The development method used is ADDIE. The research instrument uses a questionnaire to measure responses from media experts, content experts, lecturers, and students (the product users). The study reports that the product of a practical approach-based microteaching book is feasible and can be used in Biology learning. This book can be used as a guide and reference for prospective biology teacher students in determining the right microteaching model.